A family systems approach to genetic counseling: Development of narrative interventions. Issue 1 (12th January 2021) - MacLeod, Rhona; Metcalfe, Alison; Ferrer‐Duch, Mariangels
Abstract: To what extent are family systems approaches relevant in the genomics era? What difference does it make to remember the wider social context within which 'problems' associated with a genetic diagnosis reside? How does this influence the conversations we have with our patients? These questions will be considered in relation to systemic approaches to genetic counseling practice. Narrative therapy with an emphasis on people's strengths, wishes, and ways of resisting the effects of a problem may be a particularly useful framework for genetic counselors. Narrative practice views people as multi‐storied and is concerned with the question of how we encourage people to tell their stories in ways that make them feel stronger. Increased uptake of genomic testing and the number of people seeking genetic counseling present opportunities to consider new ways of working, particularly around support following a new genetic diagnosis. One option is to realize the potential of group interventions. Family therapy and narrative practices have the potential to encourage communication and for families to learn from each other.